Chasing the Other 'Populist Zeitgeist'? Mainstream Parties and the Rise of Right-Wing Populism - Michael Bayerlein (Politische Vierteljahreszeitschrift, 2021)
This article answers the question of why certain European mainstream parties have changed their policy positions on the GAL-TAN (Green/Alternative/Libertarian vs. Traditional/Authoritarian/Nationalist) dimension in recent years. I argue that these changes can be explained through the electoral success of new right-wing populist parties and the ideological proximity of conservative mainstream parties towards these parties. These arguments were tested with econometric models of mainstream parties' policy positions in 11 Western European democracies between 2002 and 2019. The results indicate that mainstream parties chase the other “populist zeitgeist” by changing their policy positions on the GAL–TAN dimension in response to the electoral success of right-wing populist parties. Mainstream parties respond to this threat by closing the distance to these parties on the GAL–TAN dimension. However, this responsiveness is largely constrained to conservative mainstream parties. The findings have important implications for understanding mainstream party responsiveness towards rivalling right-wing populist parties.
Keywords: 300; populism; electoral competition; spatial analysis; political parties; GAL-TAN dimension